The influence and practical application of Quality of Life at Work as an essential factor in leveraging production and brazilian business growth (Research, Society and Development, 2021)
The objective of this work is to portray the quality of life in the work that is a set of actions that the Brazilian companies adopt, the influence and the impacts within the business environment. The importance of coexisting in a favorable work environment makes the employees produce more, so the search for quality of life at work has been one of the subjects most addressed by companies, it is observed that keeping their employees in a pleasant social, healthy is directly connected to how the same will devote to their daily tasks, producing much more in a short time, which is a potential factor for the growth of the company. Thus, in the face of a competitive market, companies need the necessary strategic measures to motivate and satisfy the personnel and consequently increase productivity. It is perceived that the quality of life at work and productivity are directly associated with the well-being of the worker and with the organizational effectiveness, differentiated and competitive companies seek incessantly for quality in all areas, knowing that human capital is primordial, seek invest in QVT. In this article we will discuss the influence of QVT as one of the main factors for leverage in Organizational productivity and growth.